Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.22454/fammed.2019.502509
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Opioid Tapering Through Guided Instruction

Abstract: Background and Objectives: Given the current opioid epidemic, national practice guidelines and many state laws are shifting the treatment paradigm for chronic, noncancer pain to a judicious use of opioids. This has prompted a need to teach family medicine residents how to appropriately taper opioids. We created a multifaceted approach to integrate teaching of opioid tapering into a family medicine curriculum with an emphasis on guided instruction. We assessed the degree to which this curriculum affected guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Patient and public health outcomes, evaluated in less than half of the studies, included changes in patient-reported pain scores or quality of life, 18,19 unplanned access to additional medical care for pain or related issues, [20][21][22][23][24][25] concomitant opioid and benzodiazepine prescribing, [26][27][28][29][30] prescription opioid or heroin overdose hospitalizations or trends, 26,31,32 transition from acute to prolonged use after surgical procedures, 18,[33][34][35][36][37] allcause mortality, 18 patient retention rate, 28 and changes in number of prescribers or pharmacies. 26,31,38 One study also evaluated prescriber utilization of an electronic medical record (EMR) alert tool designed to facilitate compliance with OA prescribing limits.…”
Section: Resultsmentioning
confidence: 99%
“…Patient and public health outcomes, evaluated in less than half of the studies, included changes in patient-reported pain scores or quality of life, 18,19 unplanned access to additional medical care for pain or related issues, [20][21][22][23][24][25] concomitant opioid and benzodiazepine prescribing, [26][27][28][29][30] prescription opioid or heroin overdose hospitalizations or trends, 26,31,32 transition from acute to prolonged use after surgical procedures, 18,[33][34][35][36][37] allcause mortality, 18 patient retention rate, 28 and changes in number of prescribers or pharmacies. 26,31,38 One study also evaluated prescriber utilization of an electronic medical record (EMR) alert tool designed to facilitate compliance with OA prescribing limits.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, informal training allows trainees to, “put recommendations into context of patients (we) see every day.” Prior opioid education initiatives demonstrated that guided instruction (ie, informal training), with immediate application in the clinic-setting and feedback from attendings, led to greater comfort and efficiency with safe opioid tapering in residents. 41 Like in all facets of surgical education, “repeated reinforcement (leads) to recognition of patterns and learning,” and helps residents in, “seeing the effectiveness of different medications prescribed for patients on a day to day basis.” In the same way that trainees actively receive direct feedback on technical skills, opioid education should be intentional and not be considered marginal. Indeed, pedagogical research has demonstrated that deliberate practice of learned skills in a real environment, with constant feedback, is the best way to form a long-lasting, conceptual understanding of concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Prior opioid education initiatives demonstrated that guided instruction (ie, informal training), with immediate application in the clinic-setting and feedback from attendings, led to greater comfort and efficiency with safe opioid tapering in residents. 41 Like in all facets of surgical education, "repeated reinforcement (leads) to recognition of patterns and learning," and helps residents in, "seeing the effectiveness of different medications prescribed for patients on a day to day basis." In the same way that trainees actively receive direct feedback on technical skills, opioid education should be intentional and not be considered marginal.…”
Section: Real-world Applicabilitymentioning
confidence: 99%
“…5,6 One family medicine residency program has demonstrated that an educational intervention utilizing guided instruction can be effective in improving residents' guideline adherence. 7,8 Other interventions have been studied in the past, but none have explored the qualitative and quantitative value of an interdisciplinary peer-review intervention in a residency program context. [9][10][11] We developed a peer-review opioid prescribing educational intervention in a family medicine residency program, incorporating guided instruction, and examined its impact on chronic opioid prescribing practices.…”
mentioning
confidence: 99%